Currículo, gênero e nordestinidade: o que ensina o forró eletrônico? - Marlecio Maknamara da Silva Cunha (2011)
This thesis has as object the discourses of forró eletrônico songs and the gendered regulation of northeasternity. Based on post-critical theories of education, this study aimed to investigate regulations of northeasternity forged with the production of gendered subjectivities in the discourses of forró eletrônico songs. The research fits into the framework of curriculum studies that, inspired by the work of Cultural Studies and Michel Foucault, examines various discourses in their productivity over the constitution of subjects. The analysis focused on discursive fragments extracted from forró eletrônico songs, adopting elements of methodological perspectives inspired by the foucauldian analysis. The central question that guides the research is: how gendered subjectivities are regulating northeasternities in the curriculum of forró eletrônico? The thesis defended here is that forró eletrônico concurs via gender to an erosion of lines of continuity that historically forged an idea of the northeasternity. The curriculum of forró eletrônico regulates northeasternities because while it strengthens old stereotypes that have helped to cement a certain idea of what would be Northeast and its people, makes it increasingly improbable to define them through a set of precise, homogeneous and coherent discourses, images and texts in respect of gender. The analysis presented here evidence that curriculum of forró eletrônico teaches modes to be a subject in the confusion of boundaries between what would or would not proper to the northeastern in terms of gender. The thesis shows that in forró eletrônico songs are engendered continuities and discontinuities, enunciative condensations and dispersals that concentrate and dilute experiences of northeasternity. Evidence also that forró eletrônico songs are addressed in order to provide a bio-political community that imagines itself and that is imagined carrying a lifestyle that is embodied in the figure of forrozeiro/a. Therefore, the curriculum of forró eletrônico does not refuse to betray northeasternity as well as permits it to be assimilated and reinvented. In this betrayal, it shows the fiction of an invention of its own and of Northeast which allowed it.